(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
Honey is a natural liquid that is commonly used as an addition to food or drinks and has properties that are believed to increase endurance and cure various diseases. Honey has different characteristics based on taste, aroma, color. This can not be separated from the physico-chemical content of honey. High water content in honey can reduce the shelf life of honey because it can cause fermentation by yeast. So, in this study, cassava honey was processed using a vacuum cooling device designed by Mr. Anang Lastriyanto from Brawijaya University with the aim of seeing the effect of changes in honey quality on low temperature heating with vacuum pressure to reduce the water content of honey. After processing with a vacuum cooling device, the reducing sugar content, moisture content and total dissolved solids in the cassava honey are tested to show the effect of using a vacuum cooling device. Real honey has a reducing sugar content of 52.43% and after vacuum cooling it becomes 55.06%. The water content of real honey is 27.2% to 11.22 after the vacuum cooling process. The total dissolved solids of the original honey was 68.75% Brix to 79.5% Brix after vacuum cooling.